SWITCHING BEHAVIOUR AND CUSTOMER RELATIONSHIP MANAGEMENT-THE ICELAND EXPERIENCE - Mawuli Akwensivie, Divine (British Journal of Marketing Studies, 2014)
The research investigated among other things why many consumers switch from one retailer to another and effectiveness of customer relationship management as a way of improving consumer switching behavior especially in competitive food retail environment where switching behavior by customers is high. From a phemenological point that lend itself towards qualitative data, the research was conducted in two retail outlets of Iceland Food Stores in the U.K from 2004-2008 over a period of four years using a combination of different techniques that includes shop floor observations and informal discussions. The results of the study points to the fact that this aspect of food retailing is often overlooked or underestimated not by the business organizations but at store levels. Beside this customer relationship management is often misperceived and wrongly implemented and this prevented organizations from enjoying the full benefits that goes with it. The current study identified some significant factors that influenced the switching behaviour of food retail customers. Among them is the desire for bargain by consumers, increased commercials pressure from retailers, availability of choice, poor in-store service standards and delivery, attitude of cashiers and shop floor assistants. Importantly is the extent of service failure, the more serious the service failure the more likely the customer will switch even if the other factors are quite appealing. The current study concludes that these factors as identified should be subjected to a quantitative study in the future.